Loss of miR-369 Promotes Tau Phosphorylation by Targeting the Fyn and Serine/Threonine-Protein Kinase 2 Signaling Pathways in Alzheimer’s Disease Mice - Yao, Xiaoguang; Xian, Xiaohui; Fang, Mingxing; Fan, Shujuan; Li, Wenbin (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a progressive neurodegenerative dementia with the key pathological hallmarks amyloid-beta deposition and neurofibrillary tangles composed of hyperphosphorylated tau. microRNAs (miRNAs) are small noncoding RNAs that contribute to the pathogenesis of AD. In this study, we investigated the effect of the loss of miR-369 on the phosphorylation of tau protein and the activation of the kinases Fyn and SRPK2 as the upstream molecules facilitating tau phosphorylation in miR-369 knockout 3xTg-AD mice. Methods We generated miR-369 knockout 3xTg-AD mice and investigated their cognitive behaviors by maze tests. Real-time qPCR, western blot, and immunohistochemistry were performed to evaluate the expression of the miR-369 gene, phosphorylation of tau protein and activation of Fyn and SRPK2. Luciferase reporter assays were applied to confirm the predicted targets of miR-369. Results Knocking out miR-369 in 3xTg AD mice aggravated cognitive impairment, promoted hyperphosphorylation of tau, and upregulated Fyn and SRPK2. Restoring miR-369 reversed the hyperphosphorylation of tau and downregulated Fyn and SRPK2. Additionally, miR-369 was shown to target the 3’UTRs of Fyn and SRPK2 to regulate their expression levels. Conclusion Loss of miR-369 promotes tau phosphorylation by targeting the Fyn and SRPK2 signaling pathways in AD mice, and supplementation with miR-369 might be a valuable option for AD therapeutic studies.